2010
DOI: 10.1007/s10750-010-0156-4
|View full text |Cite
|
Sign up to set email alerts
|

The importance of size and growth rate in determining mercury concentrations in European minnow (Phoxinus phoxinus) and brown trout (Salmo trutta) in the subalpine lake, Øvre Heimdalsvatn

Abstract: The alien fish species, European minnow (Phoxinus phoxinus), was recorded in the mountain lake, Øvre Heimdalsvatn, southern Norway, for the first time in 1969. After some years minnows were observed in the diet of brown trout (Salmo trutta). In 2006, brown trout had significantly higher d 15 N values than European minnow, indicating that brown trout holds the top trophic position in the lake food web. The d 15 N signatures of brown trout were significantly correlated to fish size, age and mercury concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…show overdispersed distribution in fish (Halvorsen & Andersen, 1984;Kristoffersen, 1993;Knudsen & Klemetsen, 1994;Knudsen et al, 1996), as found in the present study as well, and heterogeneity among hosts in exposure to infective parasite stages is suggested to be of importance (Valtonen & Julkunen, 1995). The 13 C values of S. trutta that ranged from −30·2 to −23·0 ‰ indicate carbon sources from littoral, planktonic and benthic habitats of the lake, in accordance with the results of Jenssen et al (2010). Although the 13 C signatures in some individuals may indicate a high intake of planktonic food, there was a very low occurrence of copepods in stomach contents of S. trutta during the summer and early autumn in 2013 (present study).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…show overdispersed distribution in fish (Halvorsen & Andersen, 1984;Kristoffersen, 1993;Knudsen & Klemetsen, 1994;Knudsen et al, 1996), as found in the present study as well, and heterogeneity among hosts in exposure to infective parasite stages is suggested to be of importance (Valtonen & Julkunen, 1995). The 13 C values of S. trutta that ranged from −30·2 to −23·0 ‰ indicate carbon sources from littoral, planktonic and benthic habitats of the lake, in accordance with the results of Jenssen et al (2010). Although the 13 C signatures in some individuals may indicate a high intake of planktonic food, there was a very low occurrence of copepods in stomach contents of S. trutta during the summer and early autumn in 2013 (present study).…”
Section: Discussionsupporting
confidence: 91%
“…The low δ 15 N signatures in S. trutta from Øvre Heimdalsvatn, both in 2013 and in the study by Jenssen et al . (), indicate invertebrate feeding (Cabana & Rasmussen, , ), with no distinctly piscivorous S. trutta among the analysed individuals. The δ 15 N signals may also partly be due to the feeding on S. trutta eggs during the spawning period, as observed in autumn 2013.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Surette et al, 2006;Syväranta et al, 2006;Desta et al, 2007). However, in Øvre Heimdalsvatn there were no signs of any changes in mercury concentration in the brown trout as growth stagnated (Solhaug Jensen et al, 2010).…”
Section: Discussionmentioning
confidence: 86%